2009
DOI: 10.1016/j.jaapos.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The critical period for surgical treatment of dense congenital bilateral cataracts

Abstract: Introduction Little is known about the optimum timing of surgery for dense congenital bilateral cataracts. We examined the critical period for deprivation amblyopia in a cohort of patients with dense bilateral congenital cataracts. Methods Thirty-seven infants with dense bilateral congenital cataracts extracted by 31 weeks of age were enrolled prospectively. Visual acuity outcome was assessed at ≥5 years of age. We statistically evaluated which of 4 models provided the best fit to the data: 1) no change in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(113 citation statements)
references
References 14 publications
7
103
1
2
Order By: Relevance
“…Lambert and Drack [32] demonstrated that the equivalent latent period for bilateral visual deprivation may be as long as 10 weeks, and this correlates well with previous published studies of outcomes in infants with bilateral congenital cataracts [25,37,49]. Jain et al [28] reported that visual acuity after surgery for bilateral congenital cataracts appears to decline exponentially with duration of visual deprivation although Birch et al [10] described a bilinear model with increased deprivation amblyopia in bilateral cases operated after 14 weeks. The latent period for other visual modalities such as ocular alignment and fixation stability may be as short as 3 weeks [1].…”
Section: Aetiologysupporting
confidence: 60%
“…Lambert and Drack [32] demonstrated that the equivalent latent period for bilateral visual deprivation may be as long as 10 weeks, and this correlates well with previous published studies of outcomes in infants with bilateral congenital cataracts [25,37,49]. Jain et al [28] reported that visual acuity after surgery for bilateral congenital cataracts appears to decline exponentially with duration of visual deprivation although Birch et al [10] described a bilinear model with increased deprivation amblyopia in bilateral cases operated after 14 weeks. The latent period for other visual modalities such as ocular alignment and fixation stability may be as short as 3 weeks [1].…”
Section: Aetiologysupporting
confidence: 60%
“…Bilateral doğuşsal kataraktı olan olgularda cerrahi zamanındaki her üç haftalık gecikmenin görme keskinliğinde bir sıra düşüşe yol açtığı bildirilmiştir. 52 Şaşılığı olan olgularda kaymanın düzeltilmesi tedavide etkilidir. Ancak cerrahi başarının artması için cerrahi öncesi kapama tedavisi ile görme keskinliği arttırılmaya çalışılmalıdır.…”
Section: Nörovizyon Ve Cambridge Stimülatör (Cam) Tedavisiunclassified
“…Pediatric cataract often leads to amblyopia and secondary strabismus (1)(2)(3)(4) . Early diagnosis and treatment to prevent lateral geniculate body atrophy during the critical period of visual development is important for the visual prognosis of children affected by cataract (5)(6)(7) . Pediatric cataracts are classified according to their time of onset (chronological), etiology, and morphology.…”
Section: Introductionmentioning
confidence: 99%